Pendampingan Pengembangan Wirausaha dalam Pemanfaatan Digital Marketing: Pelatihan Pembuatan Flyer produk dengan Menggunakan Canva - Adawiyah, Wiwik Raobiatul; Tajib, Erny; Haq, Aqamal (Dirkantara Indonesia, 2023)
Micro, Small and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy. The Government has a National Economic Recovery program to help MSME with financial service institutions, the community, non-governmental organizations, and educational institutions. The role of educational institutions is very important to provide assistance and training so that MSMEs can survive and develop. Educational Institute of Human Resources Bina Amanah Entrepreneurship responded to this situation by collaborating with the Faculty of Economics and Business Trisakti University to organize Digital Marketing training for MSMEs. They gave training how to use the Canva application to create digital marketing promotional materials such as posters, flyers, or brochures for MSMEs of stalls, tailors, culinary sellers, and others. Entrepreneurs are retirees, young people who have dropped out of college or out of work, and housewives. The training is carried out in the classroom with several instructors. Participants were very enthusiastic and actively asked questions and shared experiences. The Community Service Activities of FEB Trisakti University are in accordance with the material that has been programmed, namely: 'Training on Making Product Flyers Using Canva' and was carried out well on March 4, 2023. The training is expected to increase enthusiasm for building a business and utilizing digital marketing by using the Canva application, add experience, and strengthen friendship between members of Bina Amanah. In the long term, it is hoped that MSME people can increase cooperation, excel in overcoming competition and be able to build strong collaborations to improve their business performance.